PENGEMBANGAN LKS DENGAN SCIENTIFIC APPROACH UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA - Fretty Intan Normarita; I Dewa Putu Nyeneng; Chandra Ertikanto (Jurnal Pembelajaran Fisika, 2015)
Student worksheet is one of the media used in the learning process to develop the skills, attitudes and knowledge.This development research aimed to (1) produce students worksheets, (2) knowing the interesting, (3) ease of students worksheet, and (4) effectivity of the students worksheet in terms of outcomes increase creative thinking skills. Research steps starting from need analysis, identification of resources, identification of product specifications, product development, internal testing, external testing, and production. Results of this research were (1) the development of students worksheets that can enhance creative thinking skills of students, (2) the attractiveness of the students worksheet has been categorized as very attractive value 3.34; (3) ease of students worksheet has been categorized as good with a value of 3.2; (4) the effectiveness of students worksheet has been effective with 83.3% of the students completed the KKM.Lembar kerja siswa merupakan salah satu media yang digunakan dalam proses pembelajaran untuk mengembangkan keterampilan, sikap dan pengetahuan. Penelitian ini bertujuan untuk (1) menghasilkan produk LKS, (2) mengetahui kemenarikan, (3) kemudahan LKS serta (4) keefektifitasan LKS ditinjau dari hasil peningkatan keterampilan berpikir kreatifnya. Langkah-langkah penelitian dimulai dari analisis kebutuhan, identifikasi sumber daya, identifikasi spesifikasi produk, pengembangan produk, uji internal, uji eksternal, dan produksi. Hasil dari penelitian ini adalah (1) pengembangan LKS yang dapat meningkatkan keterampilan berpikir kreatif siswa, (2) kemenarikan LKS sudah dikategorikan sangat menarik nilai 3,34; (3) kemudahan LKS sudah dikategorikan baik dengan nilai 3,2; (4) efektifitas LKS sudah efektif dengan 83,3% siswa tuntas terhadap KKM.Kata kunci: keterampilan berpikir kreatif, LKS, scientific approach.